Coping with growth transitions in successful second generation family enterprises in Singapore - Seah, May Ying (2008)
The objective of this study is to investigate the success factors and limitations of second generation Chinese Family Businesses. In trying to explain “East Asian Miracle”,researchers attribute culture as the key factor for this success. The case study methodology is adopted because it gives us the flexibility to explore each individual company in great detail with respect to scope and depth. Data was collected from interviews, newspapers, Internet and publications.